2018
DOI: 10.3390/w10091250
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Operation of Cascade Reservoirs for Flood Control of Multiple Areas Downstream: A Case Study in the Upper Yangtze River Basin

Abstract: The purpose of a flood control reservoir operation is to prevent flood damage downstream of the reservoir and the safety of the reservoir itself. When a single reservoir cannot provide enough storage capacity for certain flood control points downstream, cascade reservoirs should be operated together to protect these areas from flooding. In this study, for efficient use of the reservoir storage, an optimal flood control operation model of cascade reservoirs for certain flood control points downstream was propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 57 publications
0
20
0
1
Order By: Relevance
“…events [3,4]. Conventionally, during wet season, reservoir operators release water preferentially for flood control [5,6] while storing water before the end of wet season to meet the demand for hydropower generation, navigation, and water supply. For full replenishment of storage, reservoir operators and academic researchers have highlighted the importance of reservoir impoundment operation and impoundment rules in several studies [7][8][9][10].Reservoir operation rules are often used to provide guidelines for reservoir operators to determine the amount of controlled discharge.…”
mentioning
confidence: 99%
“…events [3,4]. Conventionally, during wet season, reservoir operators release water preferentially for flood control [5,6] while storing water before the end of wet season to meet the demand for hydropower generation, navigation, and water supply. For full replenishment of storage, reservoir operators and academic researchers have highlighted the importance of reservoir impoundment operation and impoundment rules in several studies [7][8][9][10].Reservoir operation rules are often used to provide guidelines for reservoir operators to determine the amount of controlled discharge.…”
mentioning
confidence: 99%
“…Liu et al [27] developed the hedging rules to consider economic and ecologic objectives during reservoir operation. Zhou et al [28] demonstrated how the joint operation of several reservoirs can effectively reduce the flood damage in several areas downstream.…”
Section: Optimal Reservoir Operationmentioning
confidence: 99%
“…In the joint optimal operation model of cascade reservoir systems, the minimal downstream flooding risk of the flood control objective is determined by the minimum sum of squares of the discharge flow [23,24] of the downstream reservoir, which is almost equivalent to the minimum of the largest discharge of the dam: In the joint optimal operation model of cascade reservoir systems, the minimal downstream flooding risk of the flood control objective is determined by the minimum sum of squares of the discharge flow [23,24] of the downstream reservoir, which is almost equivalent to the minimum of the largest discharge of the dam:…”
Section: Objective Functionmentioning
confidence: 99%